The in vitro hepatic microsomal metabolism of benzoic acid benzylidenehydrazide - (:unkn) unknown (Walter de Gruyter GmbH, 1997)
The in vitro hepatic microsomal metabolism of benzoic acid benzylidenehydrazide was studied using rat microsomal preparations fortified with NADPH. The substrate and its potential metabolites were synthesised and their structures were elucidated by use of their UV, IR, 1H-NMR and mass spectral characteristics. The results showed this compound produced hydrolytic metabolites, i.e. benzoic hydrazide and benzaldehyde, together with a phenolic metabolite, benzoic acid p-hydroxybenzylidene hydrazide.
Keywords: Aromatic hydroxylation; Aryl hydrazones; Metabolism in vitro